Evaluation of Advanced Potato (Solanum tuberosum L.) Clones for High Tuber yield and Processing Quality in Central Highlands of Ethiopia - Chindi, Abebe; Wgiorgis, Gebremehin; Shunka, Egata; Negash, Kasaye; Abebe, Tesfaye; Worku, Alemu; Gebretensay, Fikadu; Gebretensay, Fikadu (International journal of Horticulture, Agriculture and Food science, 2021)
In this study selected potato clones were evaluated for acceptable processing tuber attributes with yield. The most important processed potato products in the country are French fries (chips), followed by crisps. The demand for these products has increased over the years and therefore require more effort to develop varieties with appropriate qualities for the rapidly developing industry. Therefore, the experiments were conducted from 2016 to 2019 at multiple locations in the central, northwestern and south-eastern regions of Ethiopia to evaluate the performance of seven (7) advanced potato genotypes breed at the International Potato Center (CIP) and three nationally released potato varieties for high tuber yield and processing qualities during the main cropping season, June to September. The experiment was laid out in a randomized complete block design with three replications in four locations over three years. The main objective of the experiments was to select high-yielding potato clones, with suitability for processing in four agro-ecological regions of the country. Data were collected on average tuber number, tuber weight, number and weight of marketable and unmarketable tubers,and total tuber yield. Tuber physicochemical properties, dry matter content (DM), specific gravity (SG), starch content (SC), and processing products after harvests were evaluated. Moreover, the frying suitability test (IBVL) and crispness/ texture/ for the product were evaluated. Analysis of variance was performed and treatment means were compared using the Duncan multiple range test. The results revealed that there were significant differences (p<0.05) among potato clones with respect to total and marketable tuber yields, dry matter content, and specific gravity. The highest total and marketable tuber yields were obtained from Holetta and Kulumsa, while Adet and Jeldu recorded the lowest. The growing season effect on clones marketable and total tuber yield, average tuber number and weight showed highly significant. The over locations mean for total and marketable tuber yield for CIP-398190.404 was 39.90 t/ha & 35.71 t/ha, respectively followed by CIP-391058.175 with 33.31 t/ha & 30.81 t/ha. Whereas, CIP-396034.103 gave 33.77t/ha and 28.84t/ha total tuber yield and marketable tuber yield, respectively. Tuber dry matter (DM) of 25.8, 24.3, and 25.7% was recorded, respectively. While, the specific gravity (SG) of 1.09, 1.08, and 1.09 g/cm3 were obtained, respectively. The frying suitability test (IBVL) value showed that CIP-396034.103, (8.5) followed by CIP-398190.404, (7.5) and CIP-391058.175, (7.0). Among the evaluated clones, three cultivars had overall acceptable DM, SG, and frying suitability test (IBVL) for French fries and crisp processing. Thus, among the tested clones, CIP-391058.175 was registred as the first processing variety in Ethiopia.